Peran Dinas Pariwisata Provinsi Banten dalam Program Kampung Wisata Pipitan Kota Serang - Shelby Adiba Fatima Zahra; Widyastuti, Yeni (Epistemik: Indonesian Journal of Social and Political Science, 2024)
This research focuses on evaluating the evaluation of the Pipitan tourist village program in the city of Serang. This research uses a descriptive qualitative method with a qualitative approach. Tourism villages make tourism products more valuable in rural culture because there is development of tourist villages that have cultural value without destroying it. Local communities host and become important actors in the development of tourist villages at all stages, starting from the planning, monitoring and implementation stages. Pipitan Tourism Village is an interesting research object because its location coincides with the capital of Banten Province, namely Serang City. Development of the Pipitan Tourism Village into a community-based Pipitan Tourism Village by developing the role of the local community who are the managers of the Pipitan Tourism Village, such as: the chairman and members of the tourism awareness group (Pokdarwis) who are the administrators. or local residents of the Pipitan Tourism Village, MSME crafts such as flower pot crafts, garden decorations, wooden crafts, corn husk crafts are local craftsmen from the Pipitan Tourism Village. The Banten Provincial Tourism Office plays a role in distributing the budget in the development process of the Pipitan Tourism Village and the private sector will build facilities and infrastructure in the Pipitan Tourism Village. This collaboration aims to increase the economic impact, improve welfare and become a contributor to local original income in the community-based tourism sector. The concept of the Pipitan Tourism Village is very unique with a colorful concept that aims to improve the culture of the surrounding community by highlighting local characteristics such as culinary delights, and inside there is the Bolohok Market which sells regional specialties from Serang City.